1966
DOI: 10.1002/cne.901270207
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructural characterization of macroglial cell types

Abstract: In the prelaminar region of adult cat optic nerve, silver impregnation revealed a macroglial cell population consisting solely of small fibrous astrocytes. Electron microscopically the cells were characterized by abundant processes containing closely packed filaments and occasional glycogen granules; their perikarya contained few organelles, glycogen particles were conspicuous but not abundant, and their cytoplasmic and nucleoplasmic matrices were of low density.The laminar region contained typical fibrous ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
4

Year Published

1968
1968
1985
1985

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(11 citation statements)
references
References 31 publications
1
6
0
4
Order By: Relevance
“…Therefore, it was possible to consider that the occurrence of the connective tissue septa in the chicken optic nerve head might, for one thing, depend upon the existence of the pecten. However, the astrocytes in this portion possessed enriched gliofilaments, and revealed a more or less different shape than astrocytes of other portions of the optic nerve, were the same in the chicken as in the cat, monkey and man (Anderson 1969, Anderson et al 1967, Wendell-Smith 1966. Astrocytes had been found to be grouped to form the cytoplasmic septum between the retina and optic nerve in the monkey as well as the chicken optic nerve, as pointed out in this study.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Therefore, it was possible to consider that the occurrence of the connective tissue septa in the chicken optic nerve head might, for one thing, depend upon the existence of the pecten. However, the astrocytes in this portion possessed enriched gliofilaments, and revealed a more or less different shape than astrocytes of other portions of the optic nerve, were the same in the chicken as in the cat, monkey and man (Anderson 1969, Anderson et al 1967, Wendell-Smith 1966. Astrocytes had been found to be grouped to form the cytoplasmic septum between the retina and optic nerve in the monkey as well as the chicken optic nerve, as pointed out in this study.…”
Section: Discussionsupporting
confidence: 71%
“…Oligodendroglia in the chicken optic nerve possessed almost the same characteristics in ultra-fine structures as those of the rat brain (Mori and Leblond 1970), the rat optic nerve (Peters, Palay and Webster 1970), the monkey and the human optic nerve (Anderson 1969) and the cat optic nerve (Wendell-Smith 1966) ; that is, a great amount of free ribosomes and rough-surfaced endoplasmic reticulum, well-developed Golgi complex and characteristic microtubules had been pointed out to be common structures of oligodendroglia. Mori and Leblond (1970) classified the oligodendroglia in the young rat brain into three types.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Webb (1967) and many others have suggested that demyelinization seen in these chronic neurological diseases is secondary to an abnormality of the glial cells. Both astrocytes and oligodendrocytes have been shown to be able to produce myelin (Wendell-Smith et al, 1966 ;Peters, 1964). If there is a situation of increased multiplication of glial cells their increased metabolic requirements may not permit them to con-tinue to support the myelin they have produced.…”
Section: Preliminary Communicationsmentioning
confidence: 99%